ICOS+ Tregs: A Functional Subset of Tregs in Immune Diseases - Li, Dan-Yang; Xiong, Xian-Zhi (Frontiers in Immunology, 2020)
Recent studies have reported the pathological effect of ICOS+ T cells, but ICOS signals also widely participate in anti-inflammatory responses, particularly ICOS+ regulatory T (Treg) cells. The ICOS signaling pathway endows Tregs with increased generation, proliferation, and survival abilities. Furthermore, there is enough evidence to suggest a superior capacity of ICOS+ Tregs, which is partly attributable to IL-10 induced by ICOS, yet the associated mechanism needs further investigation. In this review, we discuss the complicated role of ICOS+ Tregs in several classical autoimmune diseases, allergic diseases, and cancers and investigate the related therapeutic applications in these diseases. Moreover, we identify ICOS as a potential biomarker for disease diagnosis and treatment. In addition, we believe that anti-ICOS/ICOSL monoclonal antibodies exhibit excellent clinical application potential. A thorough understanding of the effect of ICOS+ Tregs and the holistic role of ICOS towards the immune system will help to improve the therapeutic schedule of diseases.